Rancangan Sistem Aplikasi E-learning: Studi Kasus SMK Negeri 1 Pangkalpinang - Ulfa Sari Febriani; Hamidah Hamidah; Okkita Rizan (ISB Atma Luhur, 2016)
Teaching and learning process in SMK Negeri 1 Pangkalpinang are still conventional, where the students and teacher activities are only conducted in classroom. Various teaching concepts and techniques have been developed to complement the conventional methods that rely solely on a one-way method of learning andteaching in the classroom. One of teaching methods is currently being developed is e-learning. E-learning is Teachers’aid in distributing their materials where they must not attend in classroom, but use internet access. It is the best way to maximized the studying time in limited rooms.E-learning could help teaching and learning process more efficient. To realize E-learning Application in SMK Negeri 1 Pangkalpinang, it can be carried out by Learning Management System (LMS) design using Moodle. Moodle (Modular Object Oriented Dynamic Learning Environment) is one off the free LMS that can be downloaded, be utilized and be modified with a license as GPU (General Public License). The E-learning website will be used as additional discussion media for discussing unfinished learning materials, and multiple-choice exams and submitted tasks.